Solid waste treatment and disposal for rural area - Laja, D. (University Malaysia Sarawak, UNIMAS., 2006)
This thesis was conducted to get more understanding about solid waste management. Everyday life cannot be separated from discarded things such as domestic wastes. Without a good management in solid waste, the dumping of wastes will contribute to pollution. Residents in rural area facing this problem for a long term banish the domestic waste by burning it or buried it and also throwing waste into the river with a hope the waste will be carried away by river flow.